ANALISIS SISTEMATIS HUBUNGAN HIPERTENSI DENGAN RISIKO GAGAL GINJAL KRONIK - Tiar Ramadhan; Hana Nuraisa Basya (Kampus Akademik Publiser, 2025)
Hypertension is a significant risk factor for the development of chronic kidney disease (CKD). This study aims to critically analyze the relationship between hypertension and CKD risk based on recent literature. A systematic literature review (SLR) was conducted, focusing on national journals accredited by SINTA and international journals indexed by Scopus, published between 2019 and 2024. The findings indicate a consistent association between higher degrees of hypertension and increased risk of CKD. The underlying mechanisms involve elevated intraglomerular pressure, endothelial damage, and activation of the renin-angiotensin-aldosterone system (RAAS), all contributing to renal function decline. These results underscore the importance of early detection and effective management of hypertension in preventing and controlling CKD. A multidisciplinary approach, including lifestyle modifications, pharmacological therapy, and regular monitoring of renal function, is highly recommended for high-risk individuals.